History of Capoeira - Fontoura, Adriana Raquel Ritter; Guimarães, Adriana Coutinho de Azevedo (Journal of Physical Education (Maringá), 2008)
Nowadays Capoeira has a considerable importance concerning its cultural, historical and educational values. This article aimed at describing the history of Capoeira. The national bibliography was used. The literature analysis indicated that the majority of the authors consider Capoeira was brought to Brazil by black people with the purpose of fighting for surviving. Capoeira was persecuted and marginalized for a long time until it was accepted by society. The masters that emphasized and contributed for the development of capoeira was Pastinha Master and Bimba Master. The best known styles are Angola and Regional Capoeira. The instruments used to practice Capoeira are berimbau, caxixi, pandeiro, reco-reco, atabaque and agogô.